The effect of temperature and sliding speed on friction and wear of Si3N4, Al2O3, and ZrO2 balls tested against AlCrN PVD coating. (February 2018) - Antonov, M.; Afshari, H.; Baronins, J.; Adoberg, E.; Raadik, T.; Hussainova, I.
Abstract: Advanced modern materials are required to operate at challenging conditions including mutual interactions under pressure and at elevated temperatures. In the present work, unidirectional sliding tests were performed to evaluate the wear behaviour of tribo-couple of AlCrN PVD coating deposited onto a stainless steel substrate and Si3 N4, Al2 O3, and ZrO2 ceramic balls counterbodies at different speeds ranged from as low as 0.002 up to as high as 1.458 m s −1 and temperatures from 20 up to 800 °C. The wear scars were studied with the help of 3D optical surface profilometry, scanning electron microscopy, energy-dispersive and Raman spectroscopy. Bulk and flash temperatures conditioned by sliding were analytically calculated. The wear mechanisms responsible for surface degradation are detailed. Highlights: Testing of materials at high temperature in wide range of velocities is possible. Test temperature and heat generated by sliding influencing failure of materials. Maps illustrating performance of Si3 N4 -AlCrN tribocouple are prepared. Al2 O3 is the best (Si3 N4 -average; ZrO2 -worst) for 800 °C with speed up to 1.4 ms -1 . AlCrN PVD coating is reliable for high temperature sliding wear applications.